Novel transglutaminase-1 mutations and genotype–phenotype investigations of 104 patients with autosomal recessive congenital ichthyosis in the USA. Issue 2 (23rd October 2008) - Farasat, S; Wei, M-H; Herman, M; Liewehr, D J; Steinberg, S M; Bale, S J; Fleckman, P; Toro, J R
Abstract : Background: Autosomal recessive congenital ichthyosis (ARCI) is a rare hereditary disorder of cornification. Mutations in the transglutaminase-1 ( TGM1 ) gene, which encodes for the epidermal enzyme transglutaminase-1 (TGase-1), are one of the causes of ARCI. Methods: The TGM1 mutation spectrum was characterised and genotype–phenotype correlations investigated in 104 patients with ARCI ascertained through the National Registry for Ichthyosis and Related Disorders in the USA. Methods: Germline mutations in TGM1 were identified in 55% (57/104) of patients with ARCI. Arginine residues in TGase-1 were mutated in 39% (22/57) of patients overall and 54% (20/37) of those with missense mutations. In total, 55% (12/22) of missense mutations were within CpG dinucleotides and 92% (11/12) of these mutations were C→T or G→A transitions. The genotype–phenotype investigation found that ARCI with TGM1 mutations was significantly associated with presence of collodion membrane at birth (p = 0.006), ectropion (p = 0.001), plate-like scales (p = 0.005) and alopecia (p = 0.001). Patients who had at least one mutation predicted to truncate TGase-1 were more likely to have more severe hypohidrosis (p = 0.001) and overheating (p = 0.0007) at onset of symptoms than were those with exclusively TGM1 missense mutations. A logistic model was developed, which predicted that individuals with collodion membrane, alopecia and/or eye problems are about four times more likely to have TGM1 mutations than patients without these findings. Conclusion: This is the largest investigation of patients with ARCI to date. It expands the TGM1 mutation spectrum and confirms that despite genetic and phenotypic heterogeneity in ARCI, TGM1 is the main causative gene for this disorder. The high frequency of mutated arginine codons in TGM1 may be due to the deamination of CpG dinucleotides.